Evaluation of two methods of preoperative hair removal and their relationship to postoperative wound infection - Adisa, Adewale Oluseye; Lawal, Olukayode O; Adejuyigbe, Olusanya (The Journal of Infection in Developing Countries, 2011)
Introduction: When a surgical operation is to be conducted through a hair bearing part of the body, hair removal is often performed. This study aimed to evaluate the relationship of two methods of preoperative hair removal to postoperative wound infection in a developing country where razor shaving is very popular. Methodology: Consecutive consenting patients scheduled to have such operations were randomized into two groups. One group had hair removal by shaving with a razor blade while the other had hair removed by depilatory cream. Adequacy of hair removal and presence of skin injuries and/or reactions were noted preoperatively. Details of the procedures were recorded and patients were then assessed for postoperative wound infection. Results: A total of 165 patients were studied. Of the 79 patients who had hair removal by depilatory cream, hair was completely removed in 70 (88.6%) compared to 53 (61.6%) of the 86 patients who had razor hair shaving (p < 0.0001). Skin injuries were noted in 24 (27.9%) of the razor group and 3 (3.8%) of patients who had depilatory cream, (p = 0.001). Thirteen patients (7.9%) had postoperative wound infection including 2 (2.5%) in the depilatory cream group and 11 (12.8%) of the razor group. A significant association was found between preoperative skin injuries and postoperative wound infections. Conclusion: Preoperative hair removal with razor shaving predisposes to skin injuries which in turn significantly influence postoperative wound infection rates. Such injuries and resultant wound infection are fewer when depilatory cream is used for hair removal.